Struggling for Recognition: Archived-based Documentary Film of the Ahmadiyya Jamaat in Indonesia - Wulandari, Peny; Bawono, Harry (Al-Jami'ah: Journal of Islamic Studies, 2023)
The Ahmadiyya community has become a victim of persecution as labelled abnormal by other Muslim communities in Indonesia, especially in post-2004. Responding to the issue, the Ahmadiyya community constructs three colours of discourse, religious, humanitarian, and nationalism, to “normalise” their position in Indonesian society. The religious discourse stems from their direct citation to religious texts that confirm their legitimate standpoint. The humanity discourse arises from their action in the humanity program, such as blood and corneal donors. Meanwhile, the nationalism discourse appears in their short archives-based documentary film. This article examines the discourse of nationalism constructed by the Ahmadiyya via a short archives-based documentary film entitled, “Kiprah Ahmadiyah dalam Perjuangan Kemerdekaan Indonesia (the Ahmadiyya’s Role in the Struggle for the Independence of Indonesia)” using Van Dijk discourse analysis frame through an archival studies perspective. This research argues that the nationalism discourse portrayed in the film represents a deliberate act of archival activism planned by the Ahmadiyya community to seek recognition from diverse communities in Indonesia, including mainstream Muslims, general populations, and the state. [Komunitas Ahmadiyah di Indonesia telah menjadi korban persekusi karena label “tidak normal” yang disematkan oleh komunitas Muslim lain di Indonesia, terutama pasca-2004. Merespons isu tersebut, komunitas Ahmadiyah membangun tiga warna wacana: agama, kemanusiaan, dan nasionalisme. Wacana-wacana ini mereka bangun untuk “menormalkan” posisi mereka di tengah masyarakat. Wacana keagamaan dapat diidentifikasi dalam cara mereka mengutip teks-teks agama untuk mengkonfirmasi keabsahan keberadaan dan titik pijak mereka. Wacana kemanusiaan muncul dalam kegiatan mereka dalam program kemanusiaan, seperti donor darah dan kornea. Sementara, wacana nasionalisme dapat dianalisis dalam sebuah film dokumenter pendek. Artikel ini mengkaji wacana nasionalisme yang di konstruksi oleh Ahmadiyah melalui sebuah film dokumenter pendek berbasis arsip berjudul “Kiprah Ahmadiyah dalam Perjuangan Kemerdekaan Indonesia” dengan menggunakan kerangka analisis wacana Van Dijk dalam perspektif studi arsip. Penelitian ini berargumen bahwa wacana nasionalisme yang dibuat dalam film tersebut mencerminkan tindakan aktivisme-kearsipan yang direncanakan oleh komunitas Ahmadiyah untuk memperjuangkan rekognisi dari komunitas lain di Indonesia: Muslim arus utama, komunitas lain secara umum, dan negara.]